Analysis of Low-Temperature Corrosion Mechanism and Optimization of Corrosion Resistance of Air Preheater for Boiler 2 at PLTU IPP Sumsel5 - Zhiliang, Wang (Ridwan Institute, 2025)
As an important heating surface component of the boiler, the air preheater's operating condition directly affects the unit's combustion efficiency and economy. During the operation of Boiler No. 2 at PLTU IPP Sumsel5, the cold-end modules of the air preheater were exposed to a low-temperature, high-humidity, and highly acidic flue gas environment for an extended period, leading to varying degrees of low-temperature corrosion and air leakage. This resulted in an increase in the unit's exhaust gas temperature, higher load on the induced draft fan, and limited load-bearing capacity. This paper analyzes the mechanism of low-temperature corrosion at the cold end of the air preheater and proposes a technical transformation of the cold-end tube box during unit maintenance, utilizing a new tube box structure with corrosion-resistant and wear-resistant enamel protection technology. After the transformation, the operational health and reliability of the air preheater were significantly improved, the air leakage rate was reduced, boiler efficiency increased, and the plant electricity consumption rate effectively decreased, achieving excellent technical and economic outcomes. Beyond these immediate technical benefits, the retrofit demonstrates how corrosion-resistant technologies can contribute to long-term sustainability goals, reduce environmental emissions, and provide a replicable model for other power plants facing similar challenges.